Explainable machine learning for materials discovery: predicting the potentially formable Nd–Fe–B crystal structures and extracting the structure–stability relationship. (2020) - Pham, Tien-Lam; Nguyen, Duong-Nguyen; Ha, Minh-Quyet; Kino, Hiori; Miyake, Takashi; Dam, Hieu-Chi
No abstract available